Law No. 10 of The Year 1981 Promulgating The Law on The Supervision And Control of Insurance In Egypt As Amended By-Laws Nos. 307/1989 and 91/1995 = قانون الإشراف والرقابة على التأمين في مصر - Egypt; The middle east library for economic services, translator. (2025)
Law No. 10 of 1981: Promulgating The Law on The Supervision And Control of Insurance In Egypt As Amended by laws Nos 307/1989 And 91/1995 Part-I Insurance Within The Scope of This Law Part- 2 The Insurance Sector Part-3 The HHigher Insurance Council Part - 4 The Egyptian Organization For Control of Insurance Part - 5 Establishments Which are Engaged in Insurance And Re- 2. Insurance 01 Part-6 Unions And Auxiliary Agencies. Part - 7 Insurance And Re-Insurance Companies Part - 8 Registration of Insurance And Re-Insurance Companies And Licensing Them To Exercise Their Activities Part - 9 Insurance And Re-Insurance Companies' Funds And suonrängo Part - 10 Insurance of The Companies' Operations. Part - 11 Transfer of Policies - Winding Up - Cancellation of The License - Deletion of Registration. Part - 12 Insurance Experts And Agents 33 Part - 13 Companies Established According to The Provisions of The Law on Investment - As Isued by Law No. 43/1974 St Part - 14. Pen altics Part - 15 General Provisions. Part 16 Concluding Provisions. 48 Schedule of Fees Attached to Law No. 10/1981 In Connection With The Supervision And Control of Insurance In Egypt Law No. 91 For 1995: Amending Some Provistons of The Law Concerning The Supervision And Control of Insurance In Egypt, Issued As Per Law No 10 For 1861